(untitled) (Open Herald: Periodical of Methodical Research, 2026)
To assess the prevalence and causes of urinary tract infections (UTIs) and bacterial vaginosis (BV) in pregnant women, a study was conducted with 440 pregnant women. Their data were analyzed based on questionnaires and the results of urine and vaginal examinations. The odds ratio (OR) and confidence interval (CI) were calculated to determine the relationship between UTIs and BV. The results showed that the prevalence of UTIs among pregnant women was 34.3%, while the prevalence of BV was 20.8%. The percentage of women with both infections was 30.1%, while the percentage without was 14.8%. The odds ratio was 1.44, and the confidence interval (CI) at a 95% significance level was 0.95–2.19. This demonstrates a relationship between the infections, where BV predisposes to UTIs and increases the likelihood of developing them